Fuzzy classification of human skin color in color images - Boaventura, I. A.G.; Volpe, V. M.; Da Silva, I. N.; Gonzaga, A. (My University, 2006)
In this paper a fuzzy approach for the classification of skin color tones in color images is presented. The paper is divided into two stages. The first stage consists of the selection of images that contained human faces of different skin color tones. A subset made up of these images was submitted to the opinion of a group of people with the aim of classifying them into their respective skin color tones: Black, Brown, and White. In the second stage of the paper, the information obtained from the research carried out, jointly with the study of the colors and their defining tones in relation to the RGB color system, were used for the definition of the fuzzy sets as well as the inference rules implemented into the system. In this manner, the developed system is able to classify a determined color into a possible skin color. © 2006 IEEE.